The effect of axial loads on free vibration of symmetric frame structures using continuous system method - Elham Ghandi (Iranian Society of Structrual Engineering (ISSE), 2016)
The free vibration of frame structures has been usually studied in literature without considering the effect of axial loads. In this paper, the continuous system method is employed to investigate this effect on the free flexural and torsional vibration of two and three dimensional symmetric frames. In the continuous system method, in approximate analysis of buildings, commonly, the structure is replaced by an equivalent beam which matches the dominant characteristics of the structure. Accordingly, the natural frequencies of the symmetric frame structures are obtained through solving the governing differential equation of the equivalent beam whose stiffness and mass are supposed to be uniformly distributed along the length. The corresponding axial load applied to the replaced beam is calculated based on the total weight and the number of stories of the building. A numerical example is presented to show the simplicity and efficiency of the proposed solution.